Interobserver variability in the delineation of the primary lung cancer and lymph nodes on different four-dimensional computed tomography reconstructions. Issue 2 (February 2018) - Mercieca, Susan; Belderbos, José S.A.; De Jaeger, Katrien; Schinagl, Dominic A.X.; van der Voort Van Zijp, Noëlle; Pomp, Jacqueline; Theuws, Jacqueline; Khalifa, Jonathan; van de Vaart, Paul; van Herk, Marcel
Abstract: Purpose: The study compared interobserver variation in the delineation of the primary tumour (GTVp) and lymph nodes (GTVln) between three different 4DCT reconstruction types; Maximum Intensity Projection (MIP), Mid-Ventilation (Mid-V) and Mid-Position (Mid-P). Material and methods: Seven radiation oncologists delineated the GTVp and GTVln on the MIP, Mid-V and Mid-P 4DCT image reconstructions of 10 lung cancer patients. The volumes, the mean standard deviation (SD) and distribution of SD (SD/area) over the median surface contour were compared for different tumour regions. Results: The overall mean delineated volume on the MIP was significantly larger ( p  < 0.001) than the Mid-V and Mid-P. For the GTVp the Mid-P had the lowest interobserver variation (SD = 0.261 cm), followed by Mid-V (SD = 0.314 cm) and MIP (SD = 0.330 cm) For GTVln the Mid-V had the lowest interobserver variation (SD = 0.425 cm) followed by the MIP (SD = 0.477 cm) and Mid-P (SD = 0.543 cm). The SD/area distribution showed a statistically significant difference between the MIP versus Mid-P and Mid-P versus Mid-V for both GTVp and GTVln ( p  < 0.001), with outliers indicating interpretation differences for GTVp located close to the mediastinum and GTVln. Conclusion: The Mid-P reduced the interobserver variation for the GTVp. Delineation protocols must be improved to benefit from the improved image quality of Mid-P for the GTVln.